The Ocular Biometry of Adult Cataract Patients on Lifeline Express Hospital Eye-Train in Rural China - Xiaoguang Cao; Xianru Hou; Yongzhen Bao (Journal of Ophthalmology)
Aims. To describe and explore the distribution of ocular biometric parameters of adult cataract patients in rural China. Methods. Three Lifeline Express Hospital Eye-Train missions of Peking University People’s Hospital in China were chosen. 3828 adult cataract patients aged 29 to 88 years with axial length (AL) less than 27.0 mm were enrolled. The ocular biometry including visual acuity (VA), intraocular pressure, AL, corneal power (K1 and K2), and corneal endothelial counting (CEC) were collected and analysis. Corneal radius (CR) was calculated from the corneal power. Results. The participants in Zhoukou of these three missions had the worse preoperative VA (p<0.001), the lowest K1 (p<0.001), K2 (p<0.001), and K (p<0.001) and the highest K1-K2 (p<0.001), moreover AL/CR more closely to 3.0. The AL, K1-K2, and AL/CR were normally distributed. But the K1, K2, K, and CEC were not normal distributions. Except K1, all parameters were positively skewed and peaked. Conclusion. Our study provides normative ocular biometry in a large, representative rural Chinese population. The AL is normally distributed with a positive skew and big kurtosis. The corneal powers are not normal distribution. The corneal astigmatism might have a significant effect on the visual acuity.